"We’re out here risking our lives": value-of-life decisions in a prison labor program - VanderPyl, Taryn (Critical criminology, 2022)
Acceptable levels of risk exposure are calculated based on whom is at risk and how individuals in positions of power perceive the value of those at risk. This study examines how value-of-life decisions are experienced in a prison labor program. Data come from interviews with 21 adults in custody (AICs) at a forest work camp. The AICs’ narratives are compared to Oregon’s Occupational Safety and Health Standards (Oregon OSHA) for wildland firefighting that would be required if they were not incarcerated. Because incarcerated individuals are viewed as less valuable by those in power, are not considered employees, and have no legal recourse for safety standards, they are placed in more risky working environments than non-incarcerated workers.